Rola samorządu gminnego w rozwoju rekreacji ruchowej i turystyki w woj. wielkopolskim - Basińska-Zych, Agata
“The role of a local government in the development of sport for all and tourism in the example of Wielkopolska Province – research report”. The research report covers the empirical part of Agata Basinska-Zych doctoral dissertation (defended 12th June 2012), which focused on the issue of a local government influence on the development of tourism and sport for all in Poland. It is done on the basis of the chosen municipal, rural and mixed type communes of the Wielkopolska Province. The study and this report was financed from the educational resources of Ministry of Science Republic of Poland for the years 2010-2012 as a research project of supervisory character No NN 404 341 639.The main theoretical objective of research was to make an extensive analysis and assessment of the local government significance in the development of tourism and sport for all. Furthermore, the research purpose of the study was to identify the factors that decide on the local government’s activity in the process of tourism and sport for all development in the region. The other, not less important, purpose of the research, in its practical dimension, was an attempt to work out the appropriate assessment method of the local government’s involvement observed in various commune types, on the basis of the collected empirical data. Moreover, the utilitarian purpose of the study was to make a typology of communes that would consider local governments contribution into recreational and tourist development of the region. In her study, the author aspires to find the answers to the questions whether the level of local government’s activity depends on the commune’s status and what kind of factors affect the local government’s involvement in tourism and sport for all development. Methodological triangulation was used in the study. On the basis of the professional literature review, the analysis of various documents containing secondary data and own research, the author tried to make some general conclusions concerning the role of local governments in the development of tourism and sport for all, and also determine the factors stimulating local government’s activity in the development of tourism and recreation. A few research methods commonly found in different disciplines of science were applied in the thesis and in particular such as: a diagnostic survey, taxonomic methods, indicator’s methods. Moreover, for the comparative analysis purposes, some other commonly known social and economic indicators were used in the research as well as an attempt of creating own synthetic measures was taken, e.g. indicator of local government involvement/activity in tourism development and indicator of local government involvement/activity in leisure sports development.
Keywords: rekreacja ruchowa; sport dla wszystkich; turystyka; samorząd terytorialny; samorząd gminny; gminy miejskie; gminy wiejskie; gminy miejsko-wiejskie; typy gmin; rozwój lokalny; interwencjonizm samorządowy; polityka rekreacyjna; polityka turystyczna; atrakcyjność rekreacyjna gminy; atrakcyjność turystyczna gminy; analiza i ocena aktywności samorządu gminnego w rozwoju rekreacji oraz turystyki; metody wskaźnikowe; wskaźnik zaangażowania samorządu gminnego; determinanty aktywności władz lokalnych; typologie gmin; rankingi gmin; społeczność lokalna; organizacje pozarządowe; leisure sport; sport for all; tourism; local government; local authorities; municipal communities; rural communities; mixed communities; type of municipalities/communities; local development; local authority interventionism; leisure sports/recreational policy; tourism policy; recreational attraction of area; tourist attraction of area; analysis and assessment of the local government’s involvement/activity in development of sport and tourism; indicator’s methods; indicator of local government involvement/activity; determinants of local government activity; typology of communes; classification of communes; local community; non-governmental organizations